Mathematical model of laminar sublayer based on the Nikuradse experiment - Qi Yipei; Zhang Shan (矿业科学学报, 2019)
In the mine ventilation,the laminarsublayer appeared near the wall of roadway not only exerts an important influence on the formation of vortex in the core zone and the accumulation of dust and gas,but also plays a decisive role on the heat transfer,mass transfer and drag reduction with the wall.This paper based on Nikuradse experiment,a velocity distribution formula was derived by theoretical analysis a boundary between transional region and hydraulic rough region was determined.A more precise mathematical model of laminar sublayer thickness was derived and a mathematical model of boundary turbulent velocity was established,which verified that the thickness decreased as the Reynolds number increased and roughness decreased,and found that the ratio of laminar sublayer energy dissipation increased with the Reynolds number decreased and roughness increased.The results could be applied in the analysis of mine ventilation.